EDUKASI KONSEP MODERASI BERAGAMA BAGI TENAGA PENDIDIKAN TADIKA AL-FIKH ORCHARD MALAYSIA - Zuliana, Zuliana; Qorib, Muhammad; Wirian, Oktrigana; Niswa, Khairun; Butlam, Qoree (JMM (Jurnal Masyarakat Mandiri), 2025)
Abstrak: Sebagai negara dengan keragaman budaya, etnis, dan agama timbulnya tantangan dalam menjaga persatuan di tengah perbedaan. Moderasi beragama salah satu konsep penting dikuatkan sejak dini, karena kunci dalam memperkenalkan konsep moderasi beragama kepada generasi muda untuk menjawab tantangan zaman dapat tumbuh di tengah keragaman. Tenaga pendidik berperan penting untuk dapat menyampaikan pesan-pesan toleransi dan moderasi agar dapat membantu anak didik memahami agama yang moderat. Pengabdian Internasional (PKMI) kepada 50 tenaga kependidikan Tadika Al-Fikh Orchard Malaysia bertujuan meningkatkan pemahaman konsep moderasi beragama dengan metode edukasi menunjukkan peningkatan yang diperoleh melalui evaluasi. Pemberian test saat sebelum dan sesudah pelatihan dengan total pertanyaan berkisar antara 26-39 pertanyaan/indikator termasuk pre-test, post-test, kuesioner, observasi, dan diskusi. Dengan peningkatan persentase 25%.dari 60% meningkat 85 %. Dengan mengikuti edukasi menambah pemahaman peserta untuk diterapkan dalam pengajaran anak didik usia dini.Abstract: As a country with cultural, ethnic and religious diversity, there are challenges in maintaining unity amidst differences. Religious moderation is one of the important concepts to be strengthened from an early age, because the key to introducing the concept of religious moderation to the younger generation to answer the challenges of the times can grow in the midst of diversity. Educators play an important role to be able to convey messages of tolerance and moderation in order to help students understand moderate religion. International Service (PKMI) to 50 education personnel of Tadika Al-Fikh Orchard Malaysia aims to improve understanding of the concept of religious moderation with educational methods showing improvement obtained through evaluation. Giving tests before and after training with a total of questions ranging from 26-39 questions/indicators including pre-test, post-test, questionnaires, observations, and discussions. With a percentage increase of 25%, from 60% to 85%. By participating in the education, participants increased their understanding to be applied in teaching early childhood students.